Efeitos subletais de acaricidas sobre o ácaro predador Neoseiulus idaeus Denmark & Muma (Acari: Phytoseiidae) - Sousa Neto, Eduardo Pereira de (2024)
The two-spotted mite Tetranychus urticae Koch is a key pest of many crops around the world. The control o this pest mites is carried out mainly through the use of acaricides. However, the continued use of these pesticides is associated with some problems such as selection of resistant populations and sublethal effects on non-target organisms (natural enemies, pollinators, etc.). To avoid and mitigate these problems associated with pesticides, other strategies for managing this pest are being considered. The integration of different control methods (i.e., chemical control and biological control), as emphasizes the philosophy of the integrated pest management, has been an important way to reduce the speed of selection of resistant populations and reduce the frequency of pulverizations. Thus, this study was aimed to (i) evaluate the sublethal effects of acaricides used in the management of the two-spotted mite on its natural enemy Neoseiulus idaeus Denmar & Muma. The effects of the acaricides abamectin, fenpyroximate and azadirachtin on the functional and numerical response of N. idaeus was evaluated; (ii) evaluate the effects of these products on the predatory behavior of this natural enemy under different exposure scenarios. The acaricide exposure did not altered the type of functional response of N. idaeus nor the attack rate (a). However, there was a reduction in the amount of prey consumed and an increase in prey handling time (Th). Furthermore, all acaricides affected the predator's numerical response, reducing oviposition rates. In the second study, the exposure to acaricides affected the predatory behavior of N. idaeus in the exposure scenario leaf surface + prey + predator sprayed, leading to a reduction in the frequency of transitions between predator walking and meeting prey. Abamectin compromised predation regardless of the exposure scenario. All acaricides reduced the number of prey found, the number of attacks and the number of prey killed by N. idaeus. Furthermore, partial prey consumption was observed, and starving mites was observed to acaricide treatments. Our results demonstrate that abamectin is incompatible with N. idaeus.